Gender differences in non-cystic fibrosis bronchiectasis severity and bacterial load: the potential role of hormones. (September 2021) - Brooke-Hollidge, Anna; Conway, Joy; Lewis, Adam
Non cystic-fibrosis bronchiectasis (NCFB) is a complex chronic respiratory disease, characterised by excessive sputum production and abnormal permanent dilation of bronchi. Mucus accumulation leads to recurrent bacterial infections and increased bacterial load, causing vicious cycles of structural damage and decreased lung function. Respiratory physiotherapy management of NCFB includes airway clearance techniques and use of nebulised, hypertonic saline. Despite advances in treatment, a consistent relationship has been observed between gender and disease occurrence, with a higher prevalence amongst females. Furthermore, NCFB presents most aggressively amongst post-menopausal females, a group likely exposed to higher levels of progesterone (P4) over a longer period of time. The effects of gender-specific hormones on bacterial load and physiotherapy management of people living with NCFB remain unknown. The aim of this narrative review was to discuss the potential influence of gender specific hormones on NCFB disease progression and influence on physiotherapy, medical management and future research. SCOPUS and PUBMED electronic databases were used to conduct searches for relevant studies using specific inclusion and exclusion criteria. Secondary inclusion of relevant literature was obtained from primary paper references. Previous literature suggests that P4 may impair Cilia Beat Frequency (CBF) in airway epithelium. Reduction in CBF may further reduce ability to expectorate amongst individuals with NCFB, increasing bacterial load and likelihood of exacerbations, negatively impacting on disease progression. Furthermore, coadministration of Estrogen has been suggested to offer opposing effects to that of P4 only. These findings question whether hormonal levels may be monitored, controlled and optimised within management and treatment of females with NCFB to improve airway clearance, reduce exacerbations and improve quality of life. Larger scale, long-term trials are required to further explore the effects of gender specific hormones on NCFB and the viability of treatment with hormone replacement therapy. The reviews of this paper are available via the supplemental material section .